ACTIVE METHODOLOGIES: ACTIVE METHODOLOGIES AS A PEDAGOGICAL TOOL - Moreira Rodrigues, Raiderson; Ney de Lima dos Santos, Nora (Revista Gênero e Interdisciplinaridade, 2024)
This article addresses the theme “Active Methodologies: Active Methodologies as a Pedagogical Tool” and addresses the use of Active Methodologies as an innovative way to promote more meaningful and engaging learning. The article provides a comprehensive introduction to Active Methodologies, highlighting their core principles and how they differ from more traditional teaching strategies. It then discusses the practical application of these methodologies in the classroom, focusing on approaches such as problem-based learning, collaborative learning, and investment in the classroom. methodologies in the classroom. The potential benefits of using active learning methodologies are also explored, along with the challenges that educators may face when using these approaches. These benefits include greater engagement, empowerment, and application of knowledge in real-world situations. The article is based on relevant theoretical studies and references, such as the works of Araujo and Ramos (2023), Diesel, Baldez and Martins (2017), Nascimento and Coutinho (2016), Santos (2019) and others. By providing a comprehensive view of the subject, this article seeks to contribute to the understanding and adoption of Active Methodologies as a transformative pedagogical tool.